P-044 Safety of neuroangiography and neurointerventions in children: complication analysis in 509 consecutive cases. (4th July 2012) - Lin, N; Smith, E; Scott, M; Orbach, D
Abstract : Introduction/purpose: Catheter-based cerebral angiography and embolization and related techniques are important tools in the management of cerebrovascular diseases in the pediatric population. While two series reporting complication rates for pediatric diagnostic cerebral angiography have been published, a similar analysis for neurointerventional procedures in children is not available. Materials and Methods: Records for all pediatric patients who underwent cerebral angiography and/or neurointerventions from January 1, 2007 to December 31, 2010 were retrospectively reviewed to identify both intra-procedural and post-procedural complications. Events were categorized as transient non-neurological, long-term non-neurological, transient neurological and long-term neurological complications. Demographic and clinical risk factors for developing a complication were analyzed with a multivariate logistic regression model. Results: Of the 509 consecutive procedures performed by the senior author from 2007 through 2010, 304 were diagnostic angiograms and 205 were interventions. Mean age was 9.2 years (range: 4 days – 18 years), and the female to male ratio was 1.02. The interventional procedures included intracranial (85), extracranial (80), and spinal (13) embolizations, as well as sclerotherapy (27). Underlying pathology for the transarterial/transvenous interventions included Vein of Galen Malformation (23), intracranial AVM (21), intracranial AVF (17), aneurysms (16), spinal AVM (11), tumor (13), acute stroke (5), facial and extracranial AVM (53), extracranial AVF (10) and others (9). Pathologies for the sclerotherapy included venous and lymphatic malformations of the head and neck (27). Overall, zero intra-procedural and three post-procedural complications (0.99%) occurred in the diagnostic group, all of which were short-term, non-neurological events. In the interventions group, eight intra-procedural and six post-procedural complications (6.8%) were observed. There were four purely technical complications, with no clinical consequence (1.9%), four short-term non-neurological events (1.5%), three short-term neurological events (0.98%), and two long-term neurological events (0.98%): one patient developed intracerebral hemorrhage after embolization of an intracranial AVM, and another patient (a syndromic dwarf with moyamoya) had an acute infarct during aneurysm coiling. Multivariate analysis revealed that tumor embolization was associated with higher likelihood of complication than other groups of patients. There was no association between the age of the patient and the likelihood of adverse events. There were no vessel dissections or ruptures and no long-term femoral artery sequelae. Conclusions: We report safety data on the largest pediatric neurointerventional cohort to date. At a high volume pediatric neurovascular center, the complication rates for neuroangiography and embolization are low; in particular, non-transient adverse events are rare. Competing interests: None.